Punden Mbah Onggo Dongso: Tata Kelakuan dalam Legitimasi The Beyond (Studi di Dusun Tlogorejo, Desa Bumiaji, Kecamatan Bumiaji, Kota Batu) - muhammad muhammad hayat (Sociology Department, Brawijaya University, 2020)
AbstractKey words: Behavior, Legitimacy, The BeyondÂ Â Â Â Â Â Â Â Â Â Â Villagers Culture is inseparable with their vertical relation to nature. Nature is understood as a sign of caring, protecting and blessing. That concept places nature as the beyond. In the beyond, nature is placed as â€œthingâ€ which has legitimacy. This phenomenon also happens in Tlogorejo District, Bumiaji Village, Bumiaji Regency Batu City. One of â€œthingâ€ which is considered as the beyond is Punden Mbah Onggo Dá»‘ngso. Punden becomes a place where villagers go to ask for permission if they will hold or certain event such as wedding, khitan or other villagers events. It happens that the sign of nature has a lofty position as a sacred one or the beyond. This statement reflects the truly high degree of respect.Â Â Â Â Â Â Â Â Â Â Â The beyond refers to the unseen reality as the basic power which can give a sign of protection on welfare for society when that place has been understood as the way society care, keep and perform contemplation ritual. Finally the elaboration of the three concepts has encouraged the society to always remember and want to know about the good power of Punden Mbah Onggo Dongso. Therefore the society continuously consider Punden Mbah Onggo Dongso as a place to consult or ask permission before they hold whatever events they want to have.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â This research uses qualitative approach with deep analysis through verstehen method from Max Weber. The analysis is done using cyclical method from Miles and Huberman. The result shows that Punden Mbah Onggo Dongso is a from Ã²f celebrating the presence of subject. It is a process of firming the legitimacy and behavior of the collective society. And the conclusion is Punden Mbah Onggo Dongso has become a way of society in appreciating the pagan in their daily behavior norms.Â Â Â Â Â Â Â